IMPROVEMENT OF THE ORGANIZATION AND IMPLEMENTATION OF INTERNAL AUDIT SERVICES IN MINISTRIES AND AGENCIES (CASE OF THE MINISTRY OF CONSTRUCTION OF THE REPUBLIC OF UZBEKISTAN) - HAYITOV ODILJON MUSOQULOVICH (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract. In the context of public sector  modernization and fiscal discipline reforms,  internal  audit  systems  play  a  critical  role  in  ensuring  accountability, transparency,  and  performance  efficiency  within  government  institutions.  The construction  sector,  characterized  by  capital-intensive  projects,  long-term infrastructure investments, and complex procurement mechanisms, presents elevated financial, operational, and corruption-related risks. This study  aims to develop and empirically substantiate an improved model for organizing and implementing internal audit services in ministries and agencies, using the Ministry of Construction of the Republic of Uzbekistan as a case study. The research integrates institutional analysis, risk-based auditing methodology, comparative  international  benchmarking,  and  performance  indicator  modeling.  A mixed-method  research  design  was  applied,  including  document  analysis,  expert interviews (n=28), audit case evaluation (2019–2024), and quantitative modeling of internal control effectiveness indicators. Statistical analysis (correlation coefficients, regression  modeling,  risk-weighted  performance  index)  demonstrates  that  the integration of risk-based planning, digital audit platforms, and KPI-driven evaluation increases  audit  efficiency  by  27–34%  compared  to  traditional  compliance-based approaches. The scientific novelty of the research lies in proposing a digital-integrated risk-based  internal  audit  framework  tailored  to  the  construction  sector,  incorporating predictive  analytics,  performance  scoring  matrices,  and  automated  compliance tracking.  The  findings  confirm  that  strengthening  institutional  independence, introducing real-time monitoring systems, and implementing performance-based audit evaluation significantly reduce financial losses, improve project delivery timelines, and enhance governance transparency.